Air Sensitivity and Degradation Evolution of Halide Solid State Electrolytes upon Exposure. (5th November 2021) - Wang, Shuhao; Xu, Xiaowei; Cui, Can; Zeng, Cheng; Liang, Jianing; Fu, Jinzhou; Zhang, Ruiwang; Zhai, Tianyou; Li, Huiqiao
Abstract: Halide solid state electrolytes (SSEs) have attracted the attention of researchers as a new family of SSEs due to simple synthesis, high ionic conductivity, and good softness. However, until now, most of the reported works are focused on promotion of ionic conductivity, and little attention is paid to their air stability and degradation mechanism upon exposure. Herein, the degradation evolution of typical halide SSEs upon moisture is investigated in detail. It is found both Li3 InCl6 and Li3 YCl6 halide SSEs are easy to absorb water and deteriorate, and the air sensitivity is closely related to the contact area with air. In comparison, the water absorption rate of Li3 InCl6 is faster than that of Li3 YCl6, while the amount of water absorption of Li3 YCl6 is larger than that of Li3 InCl6, due to the higher solubility of InCl3 compared to YCl3 . Along with water absorption, Li3 InCl6 first forms a crystalline hydrate, then partially decomposes to InCl3 and LiCl, and InCl3 further hydrolyzes and produces acid which is corrosive; finally In2 O3 impurities are formed. Coating the surface of Li3 InCl6 with Al2 O3 can effectively improve the air stability. This work can help to understand the degradation mechanism of halide SSEs and provide guidance for the future design of new halide SSEs. Abstract : Halide solid state electrolytes are sensitive to air, gradually absorb water and, are liquefied to a transparent solution in ambient air. The air sensitivity is closely related to the contact area with air. Upon exposure, Li3 InCl6 first forms a crystalline hydrate, then partially decomposes to InCl3 and LiCl, finally In2 O3 impurities are formed.